2012
DOI: 10.1007/s10554-012-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of viral myocarditis by cardiac magnetic resonance and viral genome detection in peripheral blood

Abstract: In patients with acute myocarditis, viral genome can be detected in plasma and peripheral leukocytes. Its relationship with active myocardial inflammation, however, is not well understood. Myocardial edema as a feature of inflammation and myocardial necrosis or fibrosis can be frequently observed in patients with acute myocarditis by cardiovascular magnetic resonance (CMR). We assessed the association of viral genome presence in peripheral blood samples with myocardial edema and irreversible injury. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…Detection of viral nucleic acids in peripheral leukocytes may indicate recent viral infection, viral reactivation, or persistent infection [29]. The studies performed in patients with viral disease other than MCI have demonstrated that leukocyte samples have the highest sensitivity for viral nucleic acid detection compared to plasma and serum [30].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of viral nucleic acids in peripheral leukocytes may indicate recent viral infection, viral reactivation, or persistent infection [29]. The studies performed in patients with viral disease other than MCI have demonstrated that leukocyte samples have the highest sensitivity for viral nucleic acid detection compared to plasma and serum [30].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of nulling on the inversion scout sequence was found to be predictive of myocardial amyloid infiltration in a retrospective analysis of 39 patients [56]. The presence of myocardial edema as evidenced by T2-weighted images but not LGE was found to be predictive of the presence of viral genome in the peripheral blood in patients with viral myocarditis [57]. In related work, the elimination of T2 weighted images or early gadolinium enhancement was found to reduce the sensitivity of MRI for diagnosing acute myocarditis [58].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 93%
“…In addition to 2, 3 and 4-chamber long-axis views, 3-D short-axis volume data was acquired by steadystate free precession imaging to evaluate LV function and dimensions. Phase-contrast velocity images in the ascending aorta were obtained to measure stroke volume and rule out significant aortic insufficiency as described previously [13,15,16]. Functional and morphological data were evaluated using view forum 6.5.…”
Section: Cardiovascular Magnetic Resonance (Cmr)mentioning
confidence: 99%
“…All patients but no controls underwent ECG-triggered, T2-weighted, fast spin echo triple inversion recovery sequences (STIR) in a short axis view covering the whole left ventricle as described in our earlier studies [13,15,16]. Late gadolinium enhancement (LGE) imaging was obtained in all patients 10 minutes after iv administration of 0.2 mmol/kg gadolinium-diethylenetriaminepentaacetate using 3D inversion recovery turbo gradient echo sequences as described previously [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation